Kontroversi Paham Wahdatul Wujud Syekh Ahmad Mutamakkin (1645-1740) - Muhammad Ali; Gumilar Irfanullah; Lukman Zain; Amin Iskandar; Nurkholidah Nurkholidah (UIN Sunan Gunung Djati Bandung, 2023)
Wahdat al-Wujud (unity of being), contains the belief that humans can unite with God. The concept of one (al-wahid) and many (al-katsir), the Sufis started from the concept of Wahdat al-Wujud (unity of being), the philosophical basis for understanding God in His relationship with nature. This study aims to discuss the controversy over the Wahdatu Ideology of Shaykh Ahmad Mutamakkin. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the understanding of Wahdatul Wujud, while the material object is Syekh Ahmad Mutamakkin. The results and discussion in this study show that Syekh Ahmad Mutamakkin's Wahdatul Wujud Controversy cannot necessarily accuse him of being a heretic cleric. This study concludes that Sheikh Ahmad Mutamakkin is a great scholar who owns the book Arsy Al-Muwahidun, which contains teachings on aqidah, fiqh, and tasawuf.